Outcomes of transoral endoscopic thyroidectomy vestibular approach (TOETVA) using nerve integrity monitor (NIM) at Hanoi Medical University Hospital - Hau, Nguyen Xuan; Hien, Nguyen Xuan; Quang, Le Van; Tan, Nguyen Nhat (Tạp chí Nghiên cứu Y học, 2026)
This prospective study evaluated outcomes of Nerve Integrity Monitor (NIM) application in transoral endoscopic thyroidectomy vestibular approach (TOETVA) among 30 patients (93.3% female; mean age 39.7 years old) with benign tumors or differentiated thyroid carcinoma. Among 31 nerves at risk, anatomical variations were identified in 27.3%, including 22.6% penetrating Berry’s ligament, 22.6% passing between inferior thyroid artery branches, and 16.1% with extralaryngeal branching. NIM achieved 100% successful signal detection for initial vagus and RLN stimulation. Signal interference occurred in 46.6% but decreased with experience. Temporary RLN palsy occurred in one patient (3.3%) due to thermal injury during Berry’s ligament dissection, with complete recovery within 3 months; no permanent injury occurred. Stable intraoperative signals provided 100% negative predictive value for normal postoperative vocal cord function. NIM application in TOETVA is feasible and safe, providing reliable intraoperative guidance for RLN preservation. The high rate of anatomical variations underscores the importance of routine neuromonitoring in this approach.